EFEK POSITIF PEMBIASAAN TOILETING PADA ANAK USIA DINI DI KOBER AL MUJAHID 2, KECAMATAN PAMARICAN, KABUPATEN CIAMIS - Salamah, Siti; Mulyono, Nono; Hidayat, Yusuf (Jurnal Intisabi, 2024)
Toileting habituation is an effort to develop toilet skill that is need to be learnt as early as possible for early childhood’s life skill in the future. This study aims to determine the positive effect of toileting habituation on early childhood aged 3-4 years. In this study, the researchers used a Classroom Action Research (CAR) as the research method. This study was conducted to 10 early childhoods aged 3-4 years in Kober Al Mujahid 2, Pamarican District, Ciamis Regency, West Java. This study was carried out through 2 cycles, at which each cycle was carried out 3 times. The results of the study showed that the habit of toileting had a positive effect on early childhood, at which in the pre-cycle the percentage of early childhood was Very Good Development (BSB) with 0%. Furthermore, in the first cycle the percentage of early childhood was Very Good Development (BSB) increased up to 10%. Then, in the second cycle, the percentage of early childhood periodically increased up to 20% with the achievement of Developing Very Well (BSB). In conclusion, toileting habituation is able to have a positive effect on early childhood’s understanding in maintaining sanitation, fine motor skill, cognitive, and independence in Kober Al Mujahid 2 Bangunsari.